Perspektif pelajar terhadap faktor dan kepentingan pengajaran berkesan - Wan Rosmanira Ismail,; Zalina Mohd. Ali,; Nur Riza Mohd. Suradi,; Ummul Khair Salma Din , (Penerbit ukm, 2006)
This study is carried out to explore the factors affecting the effective teaching, and also to identify the degree of importance for each factor based on the students’ assessments. A survey was conducted to gather the data from the students at Pusat Pengajian Sains Matematik, UKM. The results obtained from the Factor Analysis showed that teaching preparation, the style of teaching and responsibility towards the students were the factors identified in effective teaching. Subsequently, the Analytical Hierarchy Process was carried out to determine the importance of each factor of effective teaching. The results showed that the teaching preparation has the highest degree of importance followed by the style of teaching, and the least important is the responsibility towards the students. The results also identified the degree of importance of each of the elements in the effective teaching factors